2017
DOI: 10.1111/een.12459
|View full text |Cite
|
Sign up to set email alerts
|

Trophic ecology of adult male Odonata. II. Dietary contributions of aquatic food sources

Abstract: Abstract. 1. Insects that emerge from rivers provide nutritional subsidies to local riparian predators. Adult damselflies and dragonflies often benefit from aquatic resources, but their high mobility and evasiveness have made it difficult to monitor their diets.2. A dual fatty acid and stable isotope analysis approach was used to investigate the links between Odonata size and behaviour with proportions of their aquatically derived nutritional sources. Additionally, the study investigated the variation in dieta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…predators), it is possible that class B metals may also exhibit biomagnification within terrestrial food chains. Although the assessment of direct trophic linkages was beyond the scope of this study, Odonata adults and riparian spiders have been shown to feed primarily on aquatic insectsa diet which can account for up to 80 and 90% of their mass, respectively (Paetzold et al, 2005;Jackson et al 2016;Chari et al, 2017). It is therefore possible that the majority of their metal exposure was due to feeding on metal-contaminated prey emerging from the contaminated freshwaters (i.e.…”
Section: ]mentioning
confidence: 99%
“…predators), it is possible that class B metals may also exhibit biomagnification within terrestrial food chains. Although the assessment of direct trophic linkages was beyond the scope of this study, Odonata adults and riparian spiders have been shown to feed primarily on aquatic insectsa diet which can account for up to 80 and 90% of their mass, respectively (Paetzold et al, 2005;Jackson et al 2016;Chari et al, 2017). It is therefore possible that the majority of their metal exposure was due to feeding on metal-contaminated prey emerging from the contaminated freshwaters (i.e.…”
Section: ]mentioning
confidence: 99%
“…Potential food sources of insect prey were also sampled to obtain reference isotope and fatty acid levels from the original source. These food sources included benthic algae and leaves from terrestrial plants [44]. Benthic algae (i.e.…”
Section: Collection Of Potential Food Sources For Batsmentioning
confidence: 99%
“…The areas of the ellipses represented the calculated fatty acid niche widths. Using fatty acids in niche analysis in this way has been successfully used in other studies [44,51]. Values of 95% credibility intervals and Bayesian posterior probabilities (P < 0.05) were used to test for significant differences between species for each location.…”
Section: Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Their ability to fly over long distances may be a challenging factor when rearing. Some insects such as adult dragonflies and damselflies are very mobile therefore little is known about which organisms they feed on and how their diets can be monitored (Chari et al, 2018). This is another challenge which has been highlighted in insect farming.…”
mentioning
confidence: 99%